Nutritional Status of Adolescents in Semi-urban Community in Dukuchhap Village of Lalitpur, Nepal - Paudel, Sudarshan; Limbu, NPM; Pradhan, PMS; Shrestha, SM; Shah, AK; Daha, SK; Baral, KP (Birat Journal of Health Sciences, 2017)
IntroductionMany Nepali adolescents (10-19 years) are undernourished, which increases the risk of morbidity and mortality. Inadequate nutrition during adolescence can retard physical growth and sexual maturation and increases the risk of adult lifestyle diseases. There is a dearth of research on the socio-demographic factors associated with the nutritional status of adolescents in Nepal.ObjectiveTo assess the nutritional status of adolescents (10-19 years) in Dukuchhap Viillage of Lalitpur, NepalMethodologyA community based descriptive cross-sectional study was carried out by medical students during their field placement for and community diagnosis in Dukuchhap Village of Lalitpur from 22th November- 19 December 2017. All 10-19 years adolescent population was included in the study. Among the total population (2545) study, 474 were adolescent. The data were collected using semi-structured questionnaire. Physical and anthropometric measurement were done. Data were analyzed using of WHO Z-scores criteria and cut offs points. All the findings were compared with Nepal Demographic and Health Survey, 2011 and other researches published in different journals on related topic. Excel version 2010 and SPSS version 13.0 were used to enter and analyze data.  ResultsThe prevalence of stunting was found out to be 36.28%.More males (16.51%) than females (12.60%) were severely stunted and 21.70% of male and 22.14% of female were moderately stunted. Among total respondents, 14.4% were severely stunted and 21.9% were moderately stunted. More numbers of male (38.2%) were stunted than female (34.7%).ConclusionPrevalence of malnutrition among adolescent was more in 10- 12 years age group. The prevalence of moderate stunting was slightly high in females than males. Adolescents with extended family type, increasing number of family members & agriculture, labourer and local business as main family occupation are more prone to suffer from malnutrition.Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 110-116